2020
DOI: 10.1021/acscentsci.0c01337
|View full text |Cite
|
Sign up to set email alerts
|

Exquisitely Specific anti-KRAS Biodegraders Inform on the Cellular Prevalence of Nucleotide-Loaded States

Abstract: Mutations to RAS proteins (H-, N-, and K-RAS) are among the most common oncogenic drivers, and tumors harboring these lesions are some of the most difficult to treat. Although covalent small molecules against KRAS G12C have shown promising efficacy against lung cancers, traditional barriers remain for drugging the more prevalent KRAS G12D and KRAS G12V mutants. Targeted degradation has emerged as an attractive alternative approach, but for KR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 72 publications
1
52
0
Order By: Relevance
“… 81 Genetic tools such as haloTag and GFP fusions have enabled the early assessment of Ub ligase compatibility, 82 while biodegraders have enabled swift scanning of POI degradation fitness for a number of E3 ligases 83 and targeting specific conformational states of KRas. 84 Collectively, these technologies offer a diverse menu to select tractable degrader starting points in live cells.…”
Section: Cellular Context Is Critical To Finding Efficient Degradersmentioning
confidence: 99%
“… 81 Genetic tools such as haloTag and GFP fusions have enabled the early assessment of Ub ligase compatibility, 82 while biodegraders have enabled swift scanning of POI degradation fitness for a number of E3 ligases 83 and targeting specific conformational states of KRas. 84 Collectively, these technologies offer a diverse menu to select tractable degrader starting points in live cells.…”
Section: Cellular Context Is Critical To Finding Efficient Degradersmentioning
confidence: 99%
“…Despite this success, the strategy of selective inhibition has problems of being applicable to only a limited range of cancers integrated with personalized medicine and cannot be used to treat cancers that lack the specific mutation. To address this gap, new approaches are being developed to more broadly target RAS either with proteases that directly cleave RAS 18 , 19 or with linkers that target RAS for cellular degradation 20 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetically encoded protein-based degraders have become increasingly popular as a proof-of-concept tools for demonstrating the validity of degrading a drug target. 48,[163][164][165] In contrast to other binding protein technology, the monobody degraders undergo minimum degradation by itself. 48,63 This may be due to the characteristic that the monobody scaffold is small and contains few lysine residues, which decrease its chance for being ubiquitinated.…”
Section: Monobody Fusions For Validating Targeted Protein Degradation Approachmentioning
confidence: 99%
“…Recently, several studies have used monobodies developed by our group for generating proteinbased degraders against several oncogenic targets by fusing a monobody directly to a subunit of E3 ligase. 48,[163][164][165] Sapkota et al first demonstrated the utility of monobodybased degraders termed AdPROMs by fusing a monobody selective to SHP2 to the VHL domain. 166 They demonstrated the feasibility of degrading endogenous RAS using NS1 monobodybased AdPROMs.…”
Section: Monobody Fusions For Validating Targeted Protein Degradation Approachmentioning
confidence: 99%